Bringing Māori Concepts into School Science: NCEA - Stewart, Georgina Tuari; Tedoldi, Angelo (Philosophy of Education Society of Australasia, 2021)
This commentary article discusses the inclusion of Māori knowledge in senior school science in the context of some new senior school science qualifications that are currently being trialled. These proposals raise challenging questions and are provoking intense debates among secondary science teachers in Aotearoa New Zealand. We introduce the proposals and their rationale and summarise the main objections raised by science teachers. We focus on three specific Māori concepts used in the proposals and comment on the possibilities.
Keywords: Māori philosophy; NCEA (National Certificate of Educational Achievement); Philosophy of science; School science; Secondary science qualifications